Pelatihan dan Pendampingan Digital Marketing bagi Pelaku UMKM Abon Tongkol Dapur Bugis - Ita Purnama; Muhamad Rizalul Fikri; Muhaimin Muhaimin (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The global advancement of technology and the internet has created vast opportunities in the business world, particularly in the digital marketing sector. The MSME "Dapur Bugis," which specializes in the production of tuna floss (abon tongkol), holds great potential for growth through the utilization of social media, especially Instagram. However, limited knowledge and digital skills remain the main obstacles in enhancing competitiveness and increasing sales revenue. This study aims to identify the problems faced by Dapur Bugis and offer solutions through digital marketing training and mentoring. The methods used include observation, interviews, needs analysis, and implementation of training. The results indicate that MSME actors improved their abilities in managing visual content, utilizing social media, and conducting effective digital promotion. Digital marketing strategies have proven effective in expanding market reach, building product branding, and positively impacting sales performance. Therefore, ongoing digital marketing training and improved digital literacy are strategic steps in strengthening MSME competitiveness in the digital era.